A standardized motor imagery introduction program (MIIP) for neuro-rehabilitation: development and evaluation - Wondrusch, Christine; Schuster, Corina (Frontiers in Human Neuroscience, 2013)
Background: For patients with central nervous system lesions and sensorimotor impairments a solid motor imagery (MI) introduction is crucial to understand and use MI to improve motor performance. The study’s aim was to develop and evaluate a standardized MI group introduction program (MIIP) for patients after stroke, multiple sclerosis, Parkinson’s disease, and traumatic brain injury. Methods: Phase 1: Based on literature a MIIP was developed comprising MI theory (definition, type, mode, perspective, planning) and MI practice (performance, control). Phase 2: Development of a 27-item self-administered MIIP evaluation questionnaire, assessing MI knowledge self-evaluation of the ability to perform MI and patient satisfaction with the MIIP. Phase 3: Evaluation of MIIP and MI questionnaire by 2 independent MI experts based on predefined criteria and 2 patients using semi-structured interviews. Phase 4: Case series with a pre-post design to evaluate MIIP (3x30minutes) using the MI questionnaire, Imaprax, Kinaesthetic and Visual Imagery Questionnaire, and Mental Chronometry. The paired t-test and the Wilcoxon signed-rank test were used to determine significant changes. Results: Data of eleven patients were analysed (5 females; age 62.3±14.1 years). Declarative MI knowledge improved significantly from 5.4±2.2 to 8.8±2.9 (p=0.010). Patients demonstrated good satisfaction with MIIP (mean satisfaction score: 83.2±11.4 %). MI ability remained on a high level but showed no significant change, except a significant decrease in the Kinaesthetic and Visual Imagery Questionnaire score. Conclusion: The presented MIIP seems to be valid and feasible for patients with central nervous system lesions and sensorimotor impairments resulting in improved MI knowledge. MIIP sessions can be held in groups of four or less. MI ability and Mental Chronometry remained unchanged after 3 training sessions.